Electronic manufacturing industry in Asia - Chai, Shin Wang (Universiti Malaysia Sarawak, (UNIMAS), 2013)
This paper examine the electronic industry manufacturing convergence in Asia, as electronic manufacturing industry is playing an important role as the backbone of countries' development in Asia. Electronic manufacturing industry is important as well in this technological advance era, and to fulfill the consumers' demand. As electronic manufacturing outsourcing becoming a great opportunity for the original manufacturing factory to source for lower cost in manufacturing, thus Asia countries is the great location for them to invest in. This is the reason that this research is important which is to find out the leading electronic manufacturing countries from in Asia I This research follows closely on Philips and Sui (2007) methodology on testing on convergence and convergence clubs clustering. Eight Asia countries are selected for this research based on their productivity which is value added divided by labour wages. The research shows that there is convergence between the 8 countries and sub-divided into 4 club clusters. India, Indonesia and Korea are in the leading countries in the industry in the first cluster, secondly is Philippine that diverged into second cluster. Following cluster included Japan, Hong Kong and Malaysia converging and the last diverging country is Singapore. Electronic manufacturing industry is important for a country to develop into high income group countries and they are focusing in increasing the productivity to improve the competitive advantage of the countries in the market.